P-102 Progesterone luteal-phase support during IUI cycle should be added depending on women age and/or on previous mid-luteal progesterone assessment to promote live births. (30th June 2022) - Petrovic, C.H; Benchaib, M; Monnier, C; Kavanagh, M; Leflon, M; Asif, S; Gardner, D; Keates, N; Medrano, J. Hernandez; Tomlison, M; Torre, A
Abstract: Study question: To determine the Mid-luteal progesterone (MLP) threshold which could condition live-birth (LB) after IUI, and effects of additional progesterone luteal-phase support (LPS) in subsequent cycles. Summary answer: MLP threshold is age-dependant. LPS should only be used if previous MLP is below the age related threshold, as its inappropriate use reduces LB rate. What is known already: Progesterone is essential to prepare and maintain the uterus suitable for a possible pregnancy. During IUI, it is not clear if LPS is beneficial to obtain a live birth, and whether it should be introduced systematically or only in women with a low MLP assessment during a previous cycle. Study design, size, duration: In an audit purpose, we performed a retrospective uni-centric analysis of 705 IUl cycles performed from January 2015 to March 2020 in couples which fertility work-up concluded to unexplained infertility, mild male infertility or PCOS with no pregnancy after 3 cycles of clomiphene citrate. Our primary outcome was LB. Participants/materials, setting, methods: IUI was performed after ovarian stimulation with gonadotrophins. MLP was assessed using immuno assay method, days 7 post-IUI. LPS (Cyclogest® 200 mg/day) was added when consultant considered former cycle's MLP was too low. MLP thresholds were defined without LPS using a ROC Curve, considering subgroups of patient's age. LB rate was analyzed using Multivariate Gill Andersen models to take into account repetitions of IUI cycles. Prognostic factors for LBR were investigated using a Cox model. Main results and the role of chance: Women were 33.6±3.9 years old. We obtained 99 (14%) LB. In women who didn't receive LPS, regardless of their age, MLP threshold was 57.5 nmo/l (AUC=0.57). Multivariate logistic regression modeling identified MLP assessment as a significant prognostic factor for obtaining LB after IUI (OR = 1.668, CI95%[1.023; 2.721], p = 0.0402). When also considering women's age, a cut-off of 36 years old was computed which allowed more fitted age-related MLP thresholds for obtaining LB after IUI. In women <36 years old, MLP threshold was 39.5 nmol/l (AUC=0.57) whereas it was 60.5 nmol/L (AUC=0.57) for age ≥36. Age-related thresholds were more predictive of LB than initial age independent threshold according to Akaike Criteria (1168.48 versus 1198.96, respectively). Using the whole population (i.e. receiving or not LPS), the multivariate analysis highlighted that, compared to women with MLP above their age related threshold who (appropriately) didn't receive LPS: - Women below their age-related MLP threshold who appropriately receive LPS had similar LB rate: OR = 0.5474, CI95%[0.1857-1.6138], p = 0.2747. - Women below their age-related MLP threshold who didn't receive LPS (inappropriately) had a significantly lower LB rate: OR = 0.4794, CI95%[0.2727-0.8427], p = 0.0106. - Women above their age-related MLP threshold who received LPS (inappropriately) had a significantly lower LB rate: OR = 0.5627, CI95%[0.3302-09587], p = 0.0433. Limitations, reasons for caution: Because of the retrospective design of our study and because of the limited number of included couples, our results should be considered with caution. Confirmation is needed with further prospective studies with a larger number of participants. Wider implications of the findings: Our study highlight for the first time the impact of age on the LPS strategy after IUI, and emphases the need for personalized fertility medicine based on previous MLP assessment when considering LPS. Trial registration number: No needed, NHS Audit